2013
DOI: 10.1103/physrevlett.111.115302
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions for a Collective Coordinate Coupled to Luttinger Liquids

Abstract: We study various realizations of collective coordinates, e.g., the position of a particle, the charge of a Coulomb box, or the phase of a Bose or a superconducting condensate, coupled to Luttinger liquids with N flavors. We find that for a Luttinger parameter ð1=2Þ < K < 1 there is a phase transition from a delocalized phase into a phase with a periodic potential at strong coupling. In the delocalized phase the dynamics is dominated by an effective mass, i.e., diffusive in imaginary time, while on the transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
4
5
0
Order By: Relevance
“…The critical value of the Luttinger parameter K c cannot be understood from the lowest order renormalization-group equations [46] and a full explanation goes beyond the scope of this work. The KT phase transitions with non-universal K c have been observed in different contexts [58,59]. Within our accuracy, the dis- appearance of ρ s coincides with the onset of the CDW order (and the charge gap (shown in Fig.…”
supporting
confidence: 66%
“…The critical value of the Luttinger parameter K c cannot be understood from the lowest order renormalization-group equations [46] and a full explanation goes beyond the scope of this work. The KT phase transitions with non-universal K c have been observed in different contexts [58,59]. Within our accuracy, the dis- appearance of ρ s coincides with the onset of the CDW order (and the charge gap (shown in Fig.…”
supporting
confidence: 66%
“…Combining numerical and analytical results [14] even showed that depending on the momentum of the particle a change in regime, from subdiffusive to polaronic, could occur. Extensions of these results to fermionic systems [15,16], driven particles [17,18] or particles coupled to several one dimensional systems [19] have since been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Giamarchi@unige.ch In particular, long-range interactions can lead to a periodic arrangement of the bath particles. New behaviors are possible in such systems, such as the localization of the impurity [26]. For a fermionic bath with nearestneighbor interactions in the Mott insulator (MI) state, a diffusive motion of the impurity was predicted to be connected to soliton excitations in the bath [27].…”
Section: Introductionmentioning
confidence: 99%